Information Asymmetry, Participation, and Long-Term Contracts - Sivaramakrishnan, K. (Management Science, 1994)
This paper examines the economic value of participative processes in the setting of long-term incentives. When informational asymmetries arise between employers (supervisors) and employees (subordinates) about future states, questions arise as to whether and when resolving these informational asymmetries produces economic gains. To address these questions, I use a two-period principal agent contracting framework in which the agent (employee) receives imperfect private information about the second period state in the first period, and make a welfare comparison between two alternative communication regimes. In the “delayed communication regime,” a report from the agent is considered only for second period contract. In the “early communication regime,” the report is considered for first period contracting as well. This regime can therefore be viewed as encouraging participation in long-term contracts. I identify conditions under which the early communication regime is strictly preferable to the delayed communication regime. Further, given some additional structure on the agent's preferences, this result obtains even if the agent can access capital markets to smooth inter-temporal consumption. Finally, I examine the setting in which the principal, at the time of contracting, has the option of whether or not to install an information system that provides the agent with private information about the future period state. I identify conditions under which installing the information system, and resolving the consequent information asymmetry through participation, is strictly preferable to not installing the information system.